Compensation expectations of employees from the Y and Z generations in the context of information society - Stankevičienė, Asta; Gerikienė, Valerija; Jurgaitytė, Neringa (Information & Media, 2016)
In the context of information society, knowledge and constant desire to learn and improve are regarded as one of the most important skills of employees. Therefore, university studies compared with the secondary and primary education are considered to be the first step towards the future career as well as it may guarantee higher income in the future. However, although it is likely that university studies in conjunction with the selected field of studies in a certain extent can determine the future earnings of the acquired profession, a number of young people overestimate expectations concerning their future rewards.According to the research results, the article examines compensation’s structural elements that influence the younger generation (Y and Z) employees’ job selection, desired salary expectations and economic and non-monetary measure incentives application in the Lithuanian market. Considering the younger employees’ future employment expectations, the article suggests some ideas for the development of human resources management policies in organisations.In order to find out Gen Y and Gen Z employees’ compensation expectations, a quantitative research based on the questionnaire method was conducted. The research included 473 respondents from the Vilnius University Faculty of Economics including bachelor’s and master's degree students from Economics, Management and Business Administration, and Business Information Systems study programs.Based on the empirical results, it was found that flexible working conditions that provide an opportunity for continuous improvement for Gen Y and Gen Z are more important than the salary level.
Keywords: ...